PEMIKIRAN ERIK H, ERIKSON TENTANG PERKEMBANGAN RELIGIUS ANAK DAN RELEVANSINYA DALAM PENDIDIKAN ISLAM - Fatimah Fatimah (Lembaga Sepercenter, 2026)
This study aims to examine Erik H. Erikson's thoughts on the psychosocial development of children and its relevance to religious development. In his theory of the eight stages of human development, Erikson emphasizes that each stage has a psychosocial crisis that must be resolved by the individual. In the early childhood stage, children are in the phase of forming trust, autonomy, and initiative. These three aspects are important foundations for personality development, including in building religious awareness and experience. This study uses a qualitative approach through a literature study by examining various relevant sources. The results of the study show that children's religious development does not stand alone but is greatly influenced by the psychosocial dynamics they experience. Trust that grows from a warm relationship with parents will form a positive image of God, while support for children's autonomy and initiative encourages a deeper internalization of religious values. Thus, the role of family and environment are key factors in instilling religious values in a healthy and sustainable manner.